“KONSELING PASTORAL MASALAH KELUARGA”: Analisis Pola Asuh Terhadap Anak Pendeta yang Berusia Remaja - Subaeda Luma; Randy A. A. P. Lombogia; Billy Kaseger (Institut Agama Kristen Negeri Manado, 2022)
The correct parenting style can educate and teach children to grow into successful individuals according to what is expected, therefore the role of parents in educating and understanding children's problems is very important. The purpose of this research is, how parents as servants of God (pastors) can understand childcare patterns, and can understand the problems of teenagers, and also know how to deal with any negative behavior or when the child makes a mistake. The researchers used descriptive qualitative research and collected data through observation and interviews with 3 boys aged 17 years who had parents as servants of God (pastors) in Manado, researchers also conducted a literature study on parenting styles. Researchers use the theory of Edwin Charis to analyze and present ideas of thought in parenting. From this research found, two concepts of thought. The First, How can parents understand every problem of teenagers. The Second, how to deal with children's negative behavior and educate their personality to match expectations, as well as ways to cultivate obedience to children, and how to discipline children, and the right way to give attention with ears that can always listen.